Ownership Structure and Stock Market Liquidity - Randi Næs (Norges Bank, 2004)
This paper studies the relationship between company ownership and market liquidity using a panel regression approach. The data sample contains detailed transactions data from a limit order driven stock market, and a full breakdown of company ownership into five distinct owner types as well as outside owner concentration and insider holdings. In line with theoretical predictions, owner concentration is found to be negatively related to spreads and information costs. A somewhat weaker negative relation is also found between spreads and insider holdings. No strong relationship can be documented between liquidity and institutional ownership. Ownership variables which affect spreads do not in general jointly affect depth in the predicted way, suggesting that spread and depth measure different dimensions of liquidity. Finally, a one-way Granger causality relation from ownership structure to liquidity is hard to document.
hdl:11250/2498547
Keywords: G10; G32; 330; market microstructure; corporate governance